Hind quarter and degree of fatness of cattle fed lipid sources in the diet - Lima, E. S.; Valente, T. N.P.; Morais, J. P.G.; Roça, R. O. [UNESP]; Deminicis, B. B. (Cordoba University Press (UCOPress), 2024)
The aim of this study was to determine the effect of the inclusion of different lipid sources (whole cottonseed and protected fat in diets containing sugar cane, corn, citrus pulp, cottonseed meal, and urea) on hind quarter (HQ) and degree of fatness (DF) of the meat of Nellore cattle during finishing in feedlot. The treatments evaluated were: feed with 2.50% cottonseed (control diet = called T1 treatment); feed with 11.50% cottonseed (high cottonseed = called T2 treatment); and feed with 3.13% cottonseed added of protected lipid (called T3 treatment), all on a dry matter basis. The forage:concentrate ratio of the diet was 50:50. Thirty nine intact steers with average initial body weight of 494 kg and 36 months of age were confined during 63 days. After this period, the animals were slaughtered and HQ and DF of the carcass were analyzed. The addition of lipid sources tested in this study did not affect the DF. However, for HQ there were differences (P <0.05) between T2 and T1, with higher HQ value in the carcass of animals that received 11.50% cottonseed. It was concluded that the addition of lipid in the diet may affect the carcass characteristics.
Quarto traseiro e gordura de cobertura de bovinos alimentados com fontes de lipídeo na dieta
Keywords: Beef cattle; Characteristics of Carcass; Protected fat; Whole cottonseed